Reversing DNA methylation pharmacologically - Yang, Allen (Henry Stewart Talks, 2010)
DNA Methylation as a target for disease therapy, Azacitidine and Decitabine are "mechanistic" inhibitors of DNA methylation, Clinical experience with DNA methylation inhibitors, Translational science of biomarkers for DNA methylation inhibitor therapy, Next generation drugs to inhibit DNA methylation